Conductive polymer dispersion and method for manufacturing the same, and capacitor and method for manufacturing the same

By using π-conjugated conductive polymer and phosphate-doped conductive polymer dispersion, the problem of high viscosity of the conductive polymer dispersion is solved, and the capacitor performance improvement of low viscosity characteristics and low ESR is achieved.

JP2025018376APending Publication Date: 2025-02-06SHIN ETSU POLYMER CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023122011
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

In the prior art, the conductive polymer dispersion has a high viscosity and is difficult to effectively penetrate into the porous dielectric layer of the capacitor or the narrow gap between the anode and the cathode, affecting the performance of the capacitor.

Method used

A conductive polymer dispersion containing a π-conjugated conductive polymer, a phosphate or a salt thereof, a polyanion and an aqueous dispersion medium is used to form a low viscosity conductive composite by doping the polyanion and the phosphate or a salt thereof, and is used to prepare a solid electrolyte layer of a capacitor.

Benefits of technology

The low viscosity characteristics of the conductive polymer dispersion are realized, easy to penetrate and form a high-performance solid electrolyte layer, reducing the equivalent series resistance (ESR) of the capacitor and improving the performance of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018376000002
    Figure 2025018376000002
  • Figure 2025018376000001
    Figure 2025018376000001
Patent Text Reader

Abstract

To provide a low-viscosity conductive polymer dispersion suitable for producing capacitors and a method for manufacturing the same, and a capacitor and a method for manufacturing the same.SOLUTION: A conductive polymer dispersion liquid containing a π-conjugated conductive polymer, a phosphonic acid or a salt thereof having a polyoxyethylene group, and an aqueous dispersion medium is used, and the conductive polymer dispersion liquid is applied to the surface of a dielectric layer formed on the surface of an anode made of a porous valve metal, for example, and dried to form a solid electrolyte layer, thereby manufacturing a capacitor.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive polymer dispersion containing a π-conjugated conductive polymer and a method for producing the same, as well as a capacitor and a method for producing the same. [Background technology]

[0002] A π-conjugated conductive polymer, whose main chain is composed of a π-conjugated system, forms a conductive complex by doping with a polyanion having an anionic group, and becomes dispersible in water. A capacitor having a solid electrolyte layer formed using a conductive polymer dispersion liquid (conductive polymer-containing liquid) in which such a conductive complex is dispersed is known (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-100744 A Summary of the Invention [Problem to be solved by the invention]

[0004] The solid electrolyte layer of the capacitor in Patent Document 1 and the like is formed by applying a conductive polymer dispersion onto a dielectric layer formed on the surface of an anode by chemical conversion treatment, and then drying and solidifying the coating. The conductive polymer dispersion to be applied is required to be able to penetrate into the porous dielectric layer and into the narrow gap between the anode and cathode, and therefore it is preferable that the viscosity of the conductive polymer dispersion used in the production of the capacitor is low.

[0005] The present invention provides a low-viscosity conductive polymer dispersion suitable for producing a capacitor and a method for producing the same, as well as a capacitor and a method for producing the same. [Means for solving the problem]

[0006] [1] A conductive polymer dispersion comprising a π-conjugated conductive polymer, a phosphonic acid or a salt thereof having a polyoxyethylene group, a polyanion, and an aqueous dispersion medium. [2] The conductive polymer dispersion according to [1], wherein the content of water relative to the total mass of the aqueous dispersion medium is 70 mass % or more. [3] The conductive polymer dispersion according to [2], wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid, or the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) and the polyanion is polystyrenesulfonic acid. [4] A method for producing a conductive polymer dispersion, comprising: a polymerization step of polymerizing a monomer that forms a π-conjugated conductive polymer in a reaction liquid containing a polyanion, a phosphonic acid having a polyoxyethylene group or a salt thereof, and an aqueous dispersion medium, to form the π-conjugated conductive polymer and a conductive complex containing the polyanion, and a phosphonic acid having a polyoxyethylene group or a salt thereof. [5] A capacitor comprising: an anode made of a porous body of a valve metal; a dielectric layer made of an oxide of the valve metal; a cathode made of a conductive material provided on the dielectric layer opposite the anode; and a solid electrolyte layer formed between the dielectric layer and the cathode, wherein the solid electrolyte layer contains a conductive complex including a π-conjugated conductive polymer, a polyanion, and a phosphonic acid or a salt thereof having a polyoxyethylene group. [6] The capacitor according to [5], wherein the solid electrolyte layer further contains a basic compound. [7] The capacitor according to [6], wherein the basic compound is a nitrogen-containing aromatic compound. [8] The capacitor according to [7], wherein the solid electrolyte layer further contains a polyol compound containing two or more hydroxyl groups. [9] The capacitor according to [8], wherein the polyol compound is diethylene glycol.

[10] A method for manufacturing a capacitor, comprising the steps of applying a conductive polymer dispersion to the surface of a dielectric layer formed on the surface of an anode made of a porous valve metal, and drying the applied conductive polymer dispersion to form a solid electrolyte layer, wherein the conductive polymer dispersion contains a conductive complex containing a π-conjugated conductive polymer and a polyanion, and a phosphonic acid or a salt thereof having a polyoxyethylene group, and an aqueous dispersion medium for dispersing the conductive complex. Effect of the Invention

[0007] Since the conductive polymer dispersion of the present invention has a low viscosity, it can be easily impregnated into an object to be coated, and is therefore suitable for producing a capacitor. According to the method for producing a conductive polymer dispersion of the present invention, a conductive polymer dispersion with low viscosity can be prepared. The capacitor of the present invention has a reduced equivalent series resistance (ESR) and excellent performance. According to the method for producing a capacitor of the present invention, the above-mentioned excellent capacitor can be easily produced.

[0008] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production."

[0009] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view showing an embodiment of a capacitor of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] ≪Conductive polymer dispersion liquid≫ A first aspect of the present invention is a conductive polymer dispersion liquid containing a π-conjugated conductive polymer, a phosphonic acid or a salt thereof having a polyoxyethylene group, a polyanion, and an aqueous dispersion medium. In the conductive polymer dispersion of this embodiment, the π-conjugated conductive polymer and the polyanion preferably form a conductive complex. The conductive complex preferably contains not only the π-conjugated conductive polymer and the polyanion, but also a phosphonic acid having a polyoxyethylene group (hereinafter sometimes abbreviated as PPA) or a salt thereof.

[0012] <Conductive composite> The conductive complex of this embodiment includes a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer to form a conductive complex having electrical conductivity. In the polyanion, only a part of the anionic groups is doped into the π-conjugated conductive polymer, and the polyanion has excess anionic groups that are not involved in the doping. Since the excess anionic groups are hydrophilic groups, the conductive complex has water dispersibility.

[0013] The conductive complex of this embodiment preferably contains PPA or a salt thereof. The phosphonic acid group of PPA can be doped into the π-conjugated conductive polymer in the same manner as the anion group of the polyanion. It is presumed that the presence of PPA or a salt thereof in the conductive complex activates molecular motion in the dispersion of the conductive complex, thereby lowering the viscosity of the dispersion.

[0014] (π-conjugated conductive polymer) The π-conjugated conductive polymer may be an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.

[0015] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable because of its excellent conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.

[0016] (Polyanion) A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer, improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer formed by polymerizing a single monomer, or a copolymer formed by polymerizing two or more types of monomers. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity.

[0017] The weight average molecular weight Mw of the polyanion is not particularly limited and is, for example, preferably from 10,000 to 1,000,000, more preferably from 50,000 to 800,000, further preferably from 100,000 to 600,000, and most preferably from 200,000 to 500,000. When the weight average molecular weight Mw of the polyanion is within the above range, the viscosity of the conductive polymer dispersion of this embodiment becomes appropriately low, and a capacitor with a sufficiently low ESR can be easily produced. The weight average molecular weight Mw of the polyanion is measured by gel filtration chromatography and is the average molecular weight based on mass calculated in terms of pullulan.

[0018] The content ratio of the polyanion contained in the conductive polymer dispersion of this embodiment is, for example, preferably in the range of 1 part by mass to 1000 parts by mass, more preferably 10 parts by mass to 700 parts by mass, and even more preferably 100 parts by mass to 500 parts by mass, relative to 100 parts by mass of the π-conjugated conductive polymer. If the content ratio of the polyanion is equal to or higher than the lower limit, the doping effect on the π-conjugated conductive polymer tends to be stronger, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or lower than the upper limit, the π-conjugated conductive polymer can be sufficiently contained, so that sufficient conductivity can be ensured.

[0019] (Phosphonic acid having a polyoxyethylene group) The polyoxyethylene group-containing phosphonic acid (PPA) or a salt thereof of this embodiment is preferably a compound represented by the following formula (1). (1) [X 1 -O-(CH 2 CH 2 O) n ] m -X 2 In the formula, X 1 represents any organic group, and X 2 represents a phosphorus atom of a phosphonic acid group, m represents 1 or 2, and n represents the number of repeats of the structural unit of the polyoxyethylene group (for example, an integer from 1 to 20). The phosphonic acid group is -P(=O)(-OH) 2 The hydroxyl group constituting the phosphonic acid group may form a salt with any cation, or may be substituted with a polyoxyethylene group represented by formula (1). Examples of the cation include alkali metals, alkaline earth metals, amine proton coordinates, and quaternary ammonium. X 1 The arbitrary organic group represented by the formula (I) is preferably a hydrocarbon group. The number of carbon atoms constituting the organic group is preferably 1 to 40, and more preferably 1 to 20. Preferable specific examples include a linear or branched alkyl group, an aryl group (aromatic hydrocarbon group), and an arylphenyl group.

[0020] PPA or its salt can be bonded to the π-conjugated conductive polymer as a dopant, similar to polyanions. When it functions as a dopant, it is considered that the phosphonic acid group is doped as an anion group. Doping with PPA or its salt reduces the viscosity of the conductive polymer dispersion, which is preferable for reducing the ESR of the solid electrolyte layer of the capacitor described later, but it may be simply included in the conductive polymer dispersion as an additive without being doped.

[0021] The conductive polymer dispersion liquid of this embodiment may contain one type of PPA or a salt thereof, or two or more types of PPA or a salt thereof. The total content ratio thereof is, for example, preferably 10 parts by mass or more and 500 parts by mass or less, more preferably 20 parts by mass or more and 200 parts by mass or less, further preferably 40 parts by mass or more and 150 parts by mass or less, and most preferably 70 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the π-conjugated conductive polymer. If the content is equal to or greater than the lower limit of the above range, the interaction with the π-conjugated conductive polymer tends to be stronger, the viscosity of the conductive polymer dispersion is lowered, and the ESR of the capacitor is further reduced. If the content is equal to or less than the upper limit of the above range, the relative content of the π-conjugated conductive polymer is increased, and sufficient conductivity can be ensured.

[0022] The mass-based content ratio, expressed as G1 / G2, of the polyanion content G1 and the PPA or a salt thereof content G2 contained in the conductive polymer dispersion of this embodiment is preferably 1.0 to 10.0, more preferably 1.5 to 8.0, even more preferably 2.0 to 6.0, particularly preferably 2.5 to 5.0, and most preferably 3.0 to 4.0. When the content is within the above range, the viscosity of the conductive polymer dispersion is reduced, and the ESR can be reduced while maintaining the capacitance of the capacitor.

[0023] The mass-based content ratio, expressed as G3 / G2, of the content G3 of the π-conjugated conductive polymer and the content G2 of the PPA or a salt thereof contained in the conductive polymer dispersion of this embodiment is preferably 0.1 to 5.0, more preferably 0.4 to 4.0, even more preferably 0.6 to 3.0, particularly preferably 0.8 to 2.5, and most preferably 1.1 to 1.9. When the content is within the above range, the viscosity of the conductive polymer dispersion is reduced, and the ESR can be reduced while maintaining the capacitance of the capacitor.

[0024] The total content of the π-conjugated conductive polymer and polyanion relative to the total mass of the conductive polymer dispersion of this embodiment is preferably from 0.1 to 5.0 mass%, more preferably from 0.5 to 2.5 mass%. When the content is within the above suitable range, the ESR of a capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced.

[0025] The content of PPA or a salt thereof relative to the total mass of the conductive polymer dispersion of this embodiment is preferably from 0.01 to 1.50 mass%, more preferably from 0.20 to 1.00 mass%, and even more preferably from 0.30 to 0.80 mass%. When the content is within the above suitable range, the ESR of a capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced.

[0026] (dispersion medium) The dispersion medium contained in the conductive polymer dispersion is preferably an aqueous dispersion medium containing water because the conductive complex is hydrophilic. Also, a dispersion medium other than water may be contained. The dispersion medium other than water is not particularly limited as long as it does not significantly impair the dispersibility of the conductive complex. Since the conductive complex has excess anion groups derived from polyanions and has high dispersibility in water, the dispersion medium other than water is preferably a water-soluble organic solvent. Here, the water-soluble organic solvent is an organic solvent that dissolves in an amount of 1 g or more in 100 g of water at 20°C, and examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvent contained as the dispersion medium may be one type or two or more types.

[0027] The content of water relative to the total mass of the dispersion medium excluding the solid content (non-volatile components) of the conductive polymer dispersion is preferably 70 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, and may be 100 mass%. When water is contained in an amount equal to or more than the above lower limit, the dispersibility of the conductive complex contained in the conductive polymer dispersion is increased, and the ESR of a capacitor having a solid electrolyte layer formed from the conductive polymer dispersion can be further reduced.

[0028] (Basic compounds) The conductive polymer dispersion may contain one or more basic compounds. The basic compound functions as a Bronsted base that receives protons from the excess anion groups of the polyanion. In order to fulfill this function, the amount of the basic compound dissolved in water is preferably 0.001 g or more per 100 g of water at 20° C. The upper limit of the amount dissolved is not particularly limited, but even if it is about 0.1 g, for example, the above function can be fulfilled sufficiently.

[0029] Examples of the basic compound that can be used include organic or inorganic basic compounds containing nitrogen, hydroxides of alkali metals or Group 2 metals, various carbonates and hydrogen carbonates, etc. Examples include hydroxides of alkali metals, quaternary ammonium hydroxides or salts thereof, ammonia, amines, etc. Specific examples of the alkali metal hydroxide include potassium hydroxide and sodium hydroxide. Specific examples of carbonates or hydrogen carbonates include ammonium hydrogen carbonate, ammonium carbonate, potassium hydrogen carbonate, potassium carbonate, sodium hydrogen carbonate, and sodium carbonate. Specific examples of the quaternary ammonium hydroxide or a salt thereof include tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrabutylammonium hydroxide.

[0030] Examples of the amine include aliphatic tertiary amines and nitrogen-containing aromatic compounds. Examples of the aliphatic tertiary amine include triethanolamine, trimethylamine, triethylamine, tripropylamine, tributylamine, trihexylamine, trioctylamine, triphenylamine, tribenzylamine, and trinaphthylamine.

[0031] Examples of nitrogen-containing aromatic compounds (aromatic compounds in which at least one nitrogen atom forms a ring structure) include pyrrole, indole, imidazole, 2-methylimidazole, 2-propylimidazole, N-methylimidazole, N-propylimidazole, N-butylimidazole, 1-(2-hydroxyethyl)imidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, and 1-cyanoethyl-2-ethyl-4-methylimidazole. Examples of the aryloxy group include 2-phenyl-4,5-dihydroxymethylimidazole, 1-acetylimidazole, 2-aminobenzimidazole, 2-amino-1-methylbenzimidazole, 2-hydroxybenzimidazole, 2-(2-pyridyl)benzimidazole, pyridine, pyrimidine, pyrazine, and derivatives thereof such as alkyl-substituted products (e.g., substituted with an alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, propyl, or butyl), halogen-substituted products (e.g., substituted with a halogen group, such as fluoro, chloro, or bromine), and nitrile-substituted products. Of these, nitrogen-containing aromatic compounds are preferred, and imidazole is more preferred.

[0032] The content of the basic compound in the conductive polymer dispersion is, for example, preferably 1 part by mass or more and 1000 parts by mass or less, more preferably 5 parts by mass or more and 100 parts by mass or less, and even more preferably 10 parts by mass or more and 50 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion. When the content is in the above preferred range, the ESR of the capacitor can be further reduced.

[0033] The content of the basic compound contained in the conductive polymer dispersion is preferably such that the pH of the conductive polymer dispersion (25°C) is 2.0 to 8.0, more preferably 2.0 to 5.0, and even more preferably 2.0 to 3.0. Within the above preferred range, the ESR of the capacitor can be further reduced.

[0034] (Polyol Compound) The conductive polymer dispersion may contain one or more polyol compounds. Here, the polyol compound refers to a compound having two or more hydroxyl groups, which is different from the π-conjugated conductive polymer, the polyanion, and the basic compound. By containing the polyol compound, the ESR of the capacitor can be further reduced.

[0035] Examples of the polyol compound include one or more selected from ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, glycerin, pentaerythritol, trimethylolpropane, and trimethylolethane.

[0036] The content of the polyol compound contained in the conductive polymer dispersion is, for example, preferably 100 parts by mass or more and 10,000 parts by mass or less, more preferably 200 parts by mass or more and 2,000 parts by mass or less, and even more preferably 300 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion. Within the above preferred range, the ESR of the capacitor can be further reduced.

[0037] The content of the polyol compound relative to the total mass of the conductive polymer dispersion is preferably from 1 to 15% by mass, more preferably from 3 to 12% by mass, and even more preferably from 5 to 9% by mass. When it is in the above preferred range, the coatability of the conductive polymer dispersion is improved, and the ESR of the capacitor can be further reduced.

[0038] (Optional Additives) The conductive polymer dispersion may contain any additive other than the conductive complex within the scope of the present invention, and the content ratio is appropriately determined depending on the type of additive, but can be, for example, 1 to 1000 parts by mass per 100 parts by mass of the total of the π-conjugated conductive polymer and the polyanion. Here, the optional additive is a compound other than the basic compound, the polyol compound, and the dispersion medium.

[0039] Examples of the optional additives include a surfactant, an inorganic conductive agent, an antifoaming agent, a coupling agent, an antioxidant, and an ultraviolet absorbing agent. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. Polymer surfactants such as polyvinyl alcohol and polyvinylpyrrolidone may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having a vinyl group, an amino group, an epoxy group, or the like. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers.

[0040] The viscosity of the conductive polymer dispersion of this embodiment at 25° C. is preferably from 1 cP to 40 cP, more preferably from 1 cP to 30 cP, even more preferably from 1 cP to 25 cP, and most preferably from 1 cP to 20 cP. When the thickness is equal to or greater than the lower limit of the above range, the thickness of the coating applied onto the dielectric layer can be ensured, making it easy to form a solid electrolyte layer of appropriate thickness. When the content is equal to or less than the upper limit of the above range, it becomes easy to cause the conductive polymer dispersion to penetrate into the fine porous structure preliminarily formed on the surface of the dielectric layer, and to form a solid electrolyte layer also inside the structure. The viscosity was measured at 25° C. using a tuning fork vibration viscometer in accordance with JIS Z8803:2011 (viscosity measurement method using a vibration viscometer).

[0041] <Method for producing conductive polymer dispersion> A second aspect of the present invention is a method for producing a conductive polymer dispersion, comprising a polymerization step of polymerizing a monomer that forms a π-conjugated conductive polymer in a reaction liquid containing a polyanion, a phosphonic acid (PPA) having a polyoxyethylene group or a salt thereof, and an aqueous dispersion medium, thereby forming a conductive complex containing the π-conjugated conductive polymer and the polyanion. The conductive polymer dispersion of the first embodiment can be produced by the production method of this embodiment.

[0042] A reaction solution containing the monomer, the polyanion, PPA or a salt thereof, and water is prepared, and the monomer is polymerized to form a π-conjugated conductive polymer. In the reaction solution, the polyanion is naturally doped into the π-conjugated conductive polymer, and a conductive complex consisting of the π-conjugated conductive polymer and the polyanion is formed. At this time, the phosphonic acid group of the PPA can be doped into the π-conjugated conductive polymer in the same manner as the anion group of the polyanion. It is presumed that the presence of PPA or a salt thereof in the conductive complex activates molecular motion in the dispersion of the conductive complex, thereby lowering the viscosity of the dispersion. From the above, the conductive complex obtained by the manufacturing method of this embodiment contains PPA or a salt thereof.

[0043] The synthesis of the conductive complex in the reaction solution can be carried out in the same manner as in the conventional synthesis of a conductive complex, except that PPA or a salt thereof is added to the reaction solution.

[0044] Since the aqueous dispersion medium contained in the reaction liquid contains water, the polymerization reaction of the monomers proceeds stably, and the resulting conductive composite is obtained in a state where it is stably dispersed in the aqueous dispersion medium. The aqueous dispersion medium may contain a dispersion medium other than water. The dispersion medium other than water may be any one that does not inhibit polymerization, and is preferably a water-soluble organic solvent. Here, the water-soluble organic solvent is an organic solvent that dissolves in 100 g of water at 20°C in an amount of 1 g or more, and examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvent contained as the dispersion medium may be one type or two or more types. The content of water relative to the total mass of the aqueous dispersion medium is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and may be 100% by mass.

[0045] It is preferable to add a known catalyst and oxidizing agent to the reaction solution to promote chemical oxidation of the monomer. Examples of the catalyst include transition metal compounds such as ferric chloride, ferric sulfate, ferric nitrate, and cupric chloride. Examples of the oxidizing agent include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate.

[0046] The amount of the catalyst to be mixed relative to the total mass of the reaction liquid (including the catalyst) is, for example, preferably from 0.01% by mass to 0.50% by mass, and more preferably from 0.01% by mass to 0.30% by mass.

[0047] The amount of the oxidizing agent relative to the total mass of the reaction liquid (including the oxidizing agent) is, for example, preferably from 0.10% by mass to 1.20% by mass, more preferably from 0.50% by mass to 1.10% by mass, and even more preferably from 0.70% by mass to 1.00% by mass.

[0048] The amount of the monomer to be mixed relative to the total mass of the reaction liquid is, for example, preferably from 0.01% by mass to 2.0% by mass, more preferably from 0.1% by mass to 1.0% by mass, and even more preferably from 0.3% by mass to 0.6% by mass. The amount of the polyanion relative to the total mass of the reaction solution is, for example, preferably 0.1% by mass to 3.0% by mass, more preferably 0.5% by mass to 2.0% by mass, and even more preferably 1.0% by mass to 1.5% by mass. By setting the content within the above preferred range, a conductive polymer dispersion having the conductive complex concentration in the above preferred content can be easily obtained.

[0049] From the viewpoint of making the content ratio of the π-conjugated conductive polymer and the polyanion in the conductive composite formed by the polymerization reaction to be the above-mentioned suitable ratio, the content ratio of the monomer and the polyanion to be mixed in the reaction solution is preferably in the range of 1 part by mass or more and 1,000 parts by mass or less, more preferably 10 parts by mass or more and 700 parts by mass or less, and even more preferably 100 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of the monomer.

[0050] The mass ratio of the amount H1 of the polyanion to be added to the reaction solution and the amount H2 of the PPA or a salt thereof, expressed as H1 / H2, is preferably 1.0 to 10.0, more preferably 1.5 to 8.0, even more preferably 2.0 to 6.0, particularly preferably 2.5 to 5.0, and most preferably 3.0 to 4.0. When the content is within the above range, the viscosity of the resulting conductive polymer dispersion is reduced, and when a capacitor is produced using this conductive polymer dispersion, the ESR can be reduced while maintaining the capacitance.

[0051] The mass ratio of the amount H3 of the monomer forming the π-conjugated conductive polymer to the amount H2 of the PPA or a salt thereof blended in the reaction solution, expressed as H3 / H2, is preferably 0.1 to 5.0, more preferably 0.4 to 4.0, further preferably 0.6 to 3.0, particularly preferably 0.8 to 2.5, and most preferably 1.1 to 1.9. When the content is within the above range, the viscosity of the resulting conductive polymer dispersion is reduced, and when a capacitor is produced using this conductive polymer dispersion, the ESR can be reduced while maintaining the capacitance.

[0052] The reaction temperature in the reaction solution can be, for example, 20 to 30° C. At the reaction temperature, the polymerization reaction is usually completed within about 4 to 12 hours. The completion of the polymerization reaction can be determined by measuring the amount of unreacted monomer in the reaction solution by gas chromatography or the like.

[0053] The catalyst and oxidizing agent added to the reaction liquid are preferably removed from the conductive polymer dispersion after the chemical oxidative polymerization of the monomer. Examples of the removal method include a method of contacting the conductive polymer dispersion with an ion exchange resin to adsorb the catalyst and oxidizing agent to the ion exchange resin, and a method of ultrafiltrating the conductive polymer dispersion to replace the dispersion medium and remove the catalyst and oxidizing agent. Among these, the method using an ion exchange resin is preferable because it is simple. It is preferable to use a cation exchange resin and an anion exchange resin in combination as the ion exchange resin.

[0054] The conductive polymer dispersion thus obtained contains the desired conductive complex. If the catalyst and oxidizing agent are removed from the reaction solution, the solution can be used as is for the production of a capacitor, which will be described later. However, the dispersion medium may be replaced with a desired one, the content concentration of the conductive complex may be adjusted, or a basic compound, a polyol compound, any additive, or the like may be added.

[0055] <<Method of manufacturing a capacitor>> A third aspect of the present invention is a method for producing a capacitor, comprising the steps of applying a conductive polymer dispersion onto a surface of a dielectric layer formed on the surface of an anode made of a porous valve metal body, and drying the applied conductive polymer dispersion to form a solid electrolyte layer. The conductive polymer dispersion contains a conductive complex containing a π-conjugated conductive polymer, a polyanion, and a phosphonic acid or a salt thereof having a polyoxyethylene group, and an aqueous dispersion medium for dispersing the conductive complex. The conductive polymer dispersion is preferably the conductive polymer dispersion of the first embodiment.

[0056] The method for manufacturing a capacitor of this embodiment preferably includes a step of oxidizing the surface of an anode made of a porous valve metal to form a dielectric layer (dielectric forming step), a step of arranging a cathode in a position facing the dielectric layer (cathode forming step), and a step of forming a solid electrolyte layer on at least a part of the surface of the dielectric layer (film forming step). Each step will be described below with reference to FIG.

[0057] [Dielectric formation process] In this step, the surface of anode 11 made of a porous valve metal is oxidized to form dielectric layer 12. The method for forming dielectric layer 12 is not particularly limited, and examples thereof include a method in which the surface of anode 11 is anodized in an electrolyte for chemical conversion treatment, such as an aqueous solution of ammonium adipate, an aqueous solution of ammonium borate, or an aqueous solution of ammonium phosphate.

[0058] [Cathode formation process] In this step, the cathode 13 is disposed at a position facing the dielectric layer 12. The method for disposing the cathode 13 is not particularly limited, and examples thereof include a method of forming the cathode 13 using a conductive paste such as a carbon paste or a silver paste, and a method of disposing a metal foil such as an aluminum foil facing the dielectric layer 12.

[0059] [Film forming process] In this step, the conductive polymer dispersion liquid described above is applied to at least a portion of the surface of the dielectric layer 12, and then dried to form the solid electrolyte layer 14.

[0060] Examples of the conductive polymer dispersion coating method include immersion (dip coating), comma coating, reverse coating, lip coating, and microgravure coating. Of these, a method of immersing the anode 11 in the conductive polymer dispersion under reduced pressure is preferred. The immersion method allows the conductive polymer dispersion to be sufficiently applied even to the inside of the porous structure on the surface of the dielectric layer 12. After immersion, the anode is removed and subjected to the next drying process.

[0061] Examples of the drying method include room temperature drying, hot air drying, far infrared drying, etc. Among these, hot air drying is preferred. The drying temperature is, for example, preferably 100 to 180° C., and more preferably 120 to 150° C. The drying time is, for example, preferably 0.2 to 1 hour. After drying, the capacitor can be assembled in the usual manner.

[0062] <Capacitor> A fourth aspect of the present invention is a capacitor comprising an anode made of a porous body of a valve metal, a dielectric layer made of an oxide of the valve metal, a cathode made of a conductive material provided on the dielectric layer opposite to the anode, and a solid electrolyte layer formed between the dielectric layer and the cathode, wherein the solid electrolyte layer contains a conductive complex including a π-conjugated conductive polymer, a polyanion, and a phosphonic acid having a polyoxyethylene group or a salt thereof. The solid electrolyte layer is preferably a cured product of the conductive polymer dispersion of the first embodiment. The capacitor of the fourth embodiment can be manufactured by the manufacturing method of the third embodiment.

[0063] An example of an embodiment of the fourth aspect will be described with reference to Fig. 1. A capacitor 10 shown in Fig. 1 includes an anode 11 made of a porous body of a valve metal, a dielectric layer 12 made of an oxide of the valve metal, a solid electrolyte layer 14 formed on the surface of the dielectric layer 12, and a cathode 13 provided on the outermost side. The cathode 13 is provided on the opposite side to the anode 11, with the dielectric layer 12 and the solid electrolyte layer 14 sandwiched therebetween.

[0064] Examples of valve metals constituting the anode 11 include aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. Among these, aluminum, tantalum, and niobium are preferable. Specific examples of the anode 11 include an aluminum foil that has been etched to increase its surface area and then oxidized, and a tantalum or niobium particle sintered body that has been oxidized and pelletized. Such a processed body is a porous body with irregularities on the surface.

[0065] The dielectric layer 12 in this embodiment is a layer formed by oxidizing the surface of the anode 11, for example, by anodizing the surface of the metallic anode 11 in an electrolyte such as an aqueous solution of ammonium adipate. Similar to the anode 11, the dielectric layer 12 also has projections and recesses.

[0066] The cathode 13 in this embodiment may be a conductive layer formed from a conductive paste or a metal layer made of a conductive material such as aluminum foil.

[0067] The solid electrolyte layer 14 in this embodiment is formed on the surface of the dielectric layer 12. The solid electrolyte layer 14 covers at least a portion of the surface of the dielectric layer 12, and may cover the entire surface of the dielectric layer 12. The thickness of the solid electrolyte layer 14 may be constant or may not be constant, and may be, for example, between 1 μm and 100 μm.

[0068] <Conductive composite> The conductive complex contained in the solid electrolyte layer contains at least a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer. The conductive complex preferably contains PPA or a salt thereof.

[0069] The total content of the π-conjugated conductive polymer, polyanion, and PPA or its salt relative to the total mass of the solid electrolyte layer is preferably 1% by mass to 99% by mass, more preferably 50% by mass to 98% by mass, and even more preferably 70% by mass to 97% by mass. The above range is preferable because it makes it easier to reduce the equivalent series resistance of the capacitor.

[0070] (Phosphonic acid having a polyoxyethylene group) The solid electrolyte layer contains a phosphonic acid having a polyoxyethylene group (PPA) or its salt, which reduces the ESR of the capacitor.

[0071] The mass ratio of the polyanion content G1' contained in the solid electrolyte layer to the PPA or a salt thereof content G2', expressed as G1' / G2', is preferably 1.0 to 10.0, more preferably 1.5 to 8.0, even more preferably 2.0 to 6.0, particularly preferably 2.5 to 5.0, and most preferably 3.0 to 4.0. Within the above range, the ESR can be reduced while maintaining the capacitance of the capacitor.

[0072] The mass ratio of the content G3' of the π-conjugated conductive polymer contained in the solid electrolyte layer to the content G2' of the PPA or a salt thereof, expressed as G3' / G2', is preferably 0.1 to 5.0, more preferably 0.4 to 4.0, further preferably 0.6 to 3.0, particularly preferably 0.8 to 2.5, and most preferably 1.1 to 1.9. Within the above range, the ESR can be reduced while maintaining the capacitance of the capacitor.

[0073] <Basic compounds> The solid electrolyte layer may further contain one or more of the above-mentioned basic compounds. By containing a basic compound, the ESR of the capacitor can be further reduced.

[0074] The content ratio of the basic compound in the solid electrolyte layer is, for example, preferably 1 part by mass or more and 1,000 parts by mass or less, more preferably 5 parts by mass or more and 100 parts by mass or less, and even more preferably 10 parts by mass or more and 50 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and the polyanion. Within the above preferred range, the ESR of the capacitor can be further reduced.

[0075] <Polyol compound> The solid electrolyte layer may further contain one or more of the above-mentioned polyols. By containing a polyol, the ESR of the capacitor can be further reduced.

[0076] The total content of the polyol compounds contained in the solid electrolyte layer is, for example, preferably 100 parts by mass or more and 10,000 parts by mass or less, more preferably 200 parts by mass or more and 2,000 parts by mass or less, and even more preferably 300 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass in total of the π-conjugated conductive polymer and polyanion contained in the solid electrolyte layer. Within the above preferred range, the ESR of the capacitor can be further reduced.

[0077] [Electrolyte] The capacitor of this embodiment may have an electrolyte that impregnates the solid electrolyte layer. Examples of the solvent constituting the electrolytic solution include alcohol-based solvents such as ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, and glycerin; lactone-based solvents such as γ-butyrolactone, γ-valerolactone, and δ-valerolactone; sulfur-based solvents such as sulfolane, dimethyl sulfoxide, and dimethyl sulfone; amide-based solvents such as N-methylformamide, N,N-dimethylformamide, N-methylacetamide, and N-methylpyrrolidinone; nitrile-based solvents such as acetonitrile and 3-methoxypropionitrile; and water. Examples of the electrolyte constituting the electrolytic solution include organic acids such as adipic acid, glutaric acid, succinic acid, benzoic acid, isophthalic acid, phthalic acid, terephthalic acid, maleic acid, toluic acid, enanthic acid, malonic acid, formic acid, decanedicarboxylic acids such as 1,6-decanedicarboxylic acid and 5,6-decanedicarboxylic acid, octanedicarboxylic acids such as 1,7-octanedicarboxylic acid, azelaic acid, and sebacic acid; or boric acid, a polyhydric alcohol complex compound of boric acid obtained from boric acid and a polyhydric alcohol; inorganic acids such as phosphoric acid, carbonic acid, and silicic acid as anion components, and primary amines (methylamine, ethylamine, propylamine, butylamine, ethylenediamine, etc.), secondary amines (dimethylamine, diethylamine, dipropylamine, methylethylamine, diphenylamine, etc.), tertiary amines (trimethylamine, triethylamine, tripropylamine, triphenylamine, 1,8-diazabicyclo(5,4,0)-undecene-7, etc.), tetraalkylammonium (tetramethylammonium, tetraethylammonium, tetrapropylammonium, tetrabutylammonium, methyltriethylammonium, dimethyldiethylammonium, etc.), etc., as a cationic component.

[0078] The capacitor of this embodiment is not limited to the above configuration, and a separator may be provided between the dielectric layer and the cathode. An example of a capacitor having a separator provided between the dielectric layer and the cathode is a wound capacitor. Examples of the separator include sheets (including nonwoven fabrics) made of cellulose, polyvinyl alcohol, polyester, polyethylene, polystyrene, polypropylene, polyimide, polyamide, polyvinylidene fluoride, etc., and nonwoven fabrics of glass fibers. The density of the separator is, for example, 0.1 g / cm 3 More than 1.0g / cm 3 The following are included: When a separator is provided, a method of forming a cathode by impregnating the separator with carbon paste or silver paste can also be applied. EXAMPLES

[0079] (Production Example 1) Production of polystyrene sulfonic acid 1 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate solution, and about 1000ml of the solvent from the obtained polystyrene sulfonic acid solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This washing operation was repeated three times. Water in the obtained solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid (PSS). 10 g of this polystyrene sulfonic acid was dissolved in 90 g of ion-exchanged water to obtain a 10% by mass aqueous solution of polystyrene sulfonic acid.

[0080] The weight average molecular weight (Mw) of the polystyrene sulfonic acid aqueous solution obtained above was measured by gel permeation chromatography (GPC) using pullulan of known weight average molecular weight as the standard substance, and the weight average molecular weight was found to be 200,000.

[0081] The weight-average molecular weight was measured using a Shimadzu Corporation high-performance liquid chromatograph Prominence, with 0.1% NaNO as the solvent. 3 An aqueous solution was used, a Shodex OHpack SB-806M HQ was used as the column, a RID-20A was used as the detector, the solvent temperature was set to 40°C, the flow rate was set to 0.6 ml / min, the PSS concentration in the sample was set to 0.1% by mass, 100 μl of the sample filtered through a membrane filter with a pore size of 0.2 μm was injected, and the analysis was performed using the analysis software Lab Solutions (Shimadzu Corporation).

[0082] (Production Example 2) Production of polystyrene sulfonic acid 2 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 0.38 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate solution, and about 1000ml of the solvent from the obtained polystyrene sulfonic acid solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid. Next, 10 g of the obtained polystyrene sulfonic acid was dissolved in 90 g of ion-exchanged water to obtain a 10% by mass aqueous polystyrene sulfonic acid solution. The weight average molecular weight of the polystyrene sulfonic acid (PSS) obtained above, measured by GPC in the same manner as in Production Example 1, was 540,000.

[0083] (Production Example 3) Preparation of Capacitor Element After connecting an anode lead terminal to the etched aluminum foil (anode foil), a voltage of 40 V was applied in a 10% by mass aqueous solution of ammonium adipate to perform chemical conversion (oxidation treatment) and form dielectric layers on both sides of the aluminum foil to obtain an anode foil. Next, opposing aluminum cathode foils to which cathode lead terminals were welded were laminated on both sides of the anode foil via a cellulose separator, and the resultant was rolled up into a cylindrical shape to obtain a capacitor element.

[0084] Example 1: Preparation of conductive polymer dispersion 5.7 g of 3,4-ethylenedioxythiophene (EDOT), 130.7 g of the polystyrene sulfonic acid (10% by mass aqueous solution) of Production Example 1, 14 g of Takesurf A-72TK65 (manufactured by Takemoto Oil Co., Ltd., polyoxyethylene alkyl ether phosphate potassium salt, 10% by mass aqueous solution), and 773.6 g of ion-exchanged water were mixed at 25°C. The resulting mixed solution was kept at 25° C., and 19.2 g of a 6% by mass aqueous solution of ferric sulfate was added while stirring. Next, 56.8 g of an 11% by mass aqueous solution of sodium persulfate was added, and the resulting reaction solution was reacted with stirring for 8 hours. By the above reaction, a conductive polymer dispersion was obtained containing a conductive complex (PEDOT-PSS-PPA) containing poly(3,4-ethylenedioxythiophene), which is a π-conjugated conductive polymer, polystyrene sulfonic acid, and polyoxyethylene alkyl ether phosphate, and water as a dispersion medium.

[0085] When the obtained conductive polymer dispersion was analyzed by GPC, the amount of unpolymerized EDOT was below the detection limit.

[0086] To this conductive polymer dispersion, 132 g of Duolite C255LFH (a cation exchange resin manufactured by Sumika Chemtex Corporation) and 132 g of Duolite A368S (anion exchange resin manufactured by Sumika Chemtex Corporation) were added, and the ion exchange resin was removed by filtration to obtain 850 g of a conductive polymer dispersion from which the oxidant and the catalyst had been removed, and the solid content (non-volatile components) was measured. Next, water was removed from the obtained conductive polymer dispersion liquid by distillation under reduced pressure using an evaporator to make the solid content 1.6 mass%. After measuring the viscosity by the method described later, imidazole was added to 100 g of the conductive polymer dispersion liquid to adjust the pH to 2.5, and 8 g of diethylene glycol was further added, and the resulting mixture was used to manufacture a capacitor.

[0087] The capacitor element obtained in Production Example 3 was immersed in the above conductive polymer dispersion liquid under reduced pressure and then dried for 30 minutes in a hot air dryer at 125°C to form a solid electrolyte layer containing a conductive complex on the surface of the dielectric layer. Next, the capacitor element having the above-mentioned solid electrolyte layer formed thereon was loaded into an aluminum case, and the case was sealed with a sealing rubber to prepare a capacitor.

[0088] Example 2 A capacitor was produced in the same manner as in Example 1, except that the amount of Takesurf A-72TK65 was 28 g and the amount of water was 759.6 g.

[0089] Example 3 A capacitor was produced in the same manner as in Example 1, except that the amount of Takesurf A-72TK65 was 42 g and the amount of water was 745.6 g.

[0090] Example 4 A capacitor was produced in the same manner as in Example 1, except that Takesurf A-7715-AQ (manufactured by Takemoto Oil Co., Ltd., polyoxyethylene arylphenyl ether phosphate amine salt, 10 mass% aqueous solution) was used instead of Takesurf A-72TK65 in Example 1.

[0091] Example 5 A capacitor was fabricated in the same manner as in Example 2, except that Takesurf A-7715-AQ was used instead of Takesurf A-72TK65.

[0092] Example 6 A capacitor was fabricated in the same manner as in Example 3, except that Takesurf A-7715-AQ was used instead of Takesurf A-72TK65.

[0093] Example 7 A capacitor was produced in the same manner as in Example 1, except that the amount of polystyrene sulfonic acid (10% by mass aqueous solution) in Production Example 1 was changed from 130.7 g to 91.3 g, and the amount of water was changed to 813.0 g.

[0094] Example 8 A capacitor was produced in the same manner as in Example 1, except that 130.7 g of polystyrene sulfonic acid (10% by mass aqueous solution, Mw: 200,000) of Production Example 1 was replaced with 130.7 g of polystyrene sulfonic acid (10% by mass aqueous solution, Mw: 540,000) of Production Example 2.

[0095] Comparative Example 1 A capacitor was produced in the same manner as in Example 1, except that Takesurf A-72TK65 was not added. Comparative Example 2 A capacitor was produced in the same manner as in Example 7, except that Takesurf A-72TK65 was not added. Comparative Example 3 A capacitor was produced in the same manner as in Example 8, except that Takesurf A-72TK65 was not added. Comparative Example 4 An investigation was carried out in the same manner as in Example 1 except that polystyrene sulfonic acid was not added. However, particles were precipitated and a conductive polymer dispersion liquid could not be obtained, so the investigation was discontinued.

[0096] [pH measurement] The pH was measured at 25°C by a conventional method using a commercially available pH meter.

[0097] [Method of measuring viscosity] The conductive polymer dispersion with a solid content of 1.6% by mass obtained in each example (however, imidazole and the additional 8 g of diethylene glycol were not added) was dispersed using a high-pressure homogenizer, and the viscosity of the conductive polymer dispersion was measured at 25°C using a tuning fork vibration viscometer (model number: SV-10, manufactured by A&D Corporation) in accordance with JIS Z8803:2011 (viscosity measurement method using a vibration viscometer). 1 Pa s (pascal second) was converted to 1000 cP (centipoise).

[0098] <Evaluation> (Production Example 4) Production of Capacitor The capacitor element was immersed under reduced pressure in the conductive polymer dispersion containing imidazole and diethylene glycol obtained in each example, and then dried for 20 minutes in a hot air dryer at 120°C twice to form a solid electrolyte layer containing a conductive complex on the surface of the dielectric layer. Furthermore, the capacitor element was loaded into an aluminum case and sealed with a sealing rubber to prepare a capacitor.

[0099] [Capacitance and equivalent series resistance measurements] The capacitance (unit: μF) at 120 Hz and the equivalent series resistance (ESR) (unit: mΩ) at 100 kHz of the capacitors prepared using the conductive polymer dispersions of each example were measured using an LCR meter ZM2376 (NF Corporation). The measurement results are shown in Table 1.

[0100] [Table 1]

[0101] <Result> The conductive polymer dispersion of the examples contained a phosphonic acid (PPA) having a polyoxyethylene group or a salt thereof together with a π-conjugated conductive polymer and a polyanion as a conductive complex, and therefore had a reduced viscosity. Compared with Comparative Examples 1 to 3 in which PPA or a salt thereof was not blended, the viscosity of the conductive polymer dispersion of the examples containing PPA or a salt thereof was significantly reduced, and therefore it is understood that the PEDOT-PSS complex of the examples contains PPA or a salt thereof. Since PPA has a phosphonic acid group, it is considered to be doped into PEDOT in the same way as PSS. In addition, in the capacitor manufactured using the conductive polymer dispersion of the embodiment, the ESR could be reduced while maintaining the capacitance. The viscosity of the conductive polymer dispersion was reduced as the amount of PPA or its salt contained in the conductive polymer dispersion increased, and the ESR of the capacitor tended to decrease.

[0102] On the other hand, the conductive polymer dispersions of Comparative Examples 1 to 3 did not contain PPA or its salt, and therefore had high viscosity and the ESR of the capacitor was poor. In Comparative Example 4, since no polyanion was added, a conductive composite dispersible in an aqueous dispersion was not obtained, and a capacitor could not be manufactured. From these results, it is understood that in each Example, PPA or a salt thereof is contained in the conductive complex, forming PEDOT-PSS-PPA and being stably dispersed in the aqueous solvent. [Explanation of symbols]

[0103] 10 Capacitor 11 Anode 12 Dielectric layer 13 Cathode 14 Solid electrolyte layer

Claims

1. A conductive polymer dispersion liquid comprising a π-conjugated conductive polymer, a phosphonic acid or a salt thereof having a polyoxyethylene group, a polyanion, and an aqueous dispersion medium.

2. The conductive polymer dispersion according to claim 1 , wherein the content of water relative to the total mass of the aqueous dispersion medium is 70 mass % or more.

3. The π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid, or 3. The conductive polymer dispersion according to claim 2, wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) and the polyanion is polystyrenesulfonic acid.

4. A monomer for forming a π-conjugated conductive polymer is polymerized in a reaction solution containing a polyanion, a phosphonic acid or a salt thereof having a polyoxyethylene group, and an aqueous dispersion medium, A method for producing a conductive polymer dispersion, comprising a polymerization step of forming a conductive complex containing the π-conjugated conductive polymer, the polyanion, and a phosphonic acid or a salt thereof having a polyoxyethylene group.

5. The present invention relates to a valve metal porous body, and a cathode made of a conductive material and provided on the dielectric layer opposite to the anode. A capacitor, wherein the solid electrolyte layer contains a conductive complex containing a π-conjugated conductive polymer, a polyanion, and a phosphonic acid or a salt thereof having a polyoxyethylene group.

6. The capacitor according to claim 5 , wherein the solid electrolyte layer further contains a basic compound.

7. The capacitor of claim 6 , wherein the basic compound is a nitrogen-containing aromatic compound.

8. The capacitor according to claim 7 , wherein the solid electrolyte layer further contains a polyol compound containing two or more hydroxyl groups.

9. The capacitor of claim 8 , wherein the polyol compound is diethylene glycol.

10. 1. A method for manufacturing a capacitor, comprising the steps of: applying a conductive polymer dispersion onto a surface of a dielectric layer formed on a surface of an anode made of a porous valve metal; and drying the applied conductive polymer dispersion to form a solid electrolyte layer, The conductive polymer dispersion liquid comprises a conductive complex containing a π-conjugated conductive polymer and a polyanion, and a phosphonic acid or a salt thereof having a polyoxyethylene group, and an aqueous dispersion medium for dispersing the conductive complex.

Citation Information

Patent Citations

  • Capacitor and method for producing the same, and conductive polymer dispersion

    JP2020100744A